A safe and effective endoscopic treatment method for simple hepatic cysts (with video) - Chen, Congying; Han, Xiao; Xiao, Wenqin; Xu, Gang; Cai, Xiaobo; Hu, Guoyong; Wan, Rong (Endoscopy International Open, 2024)
Background and study aims Symptomatic simple hepatic cysts require treatment, with several guidelines recommending laparoscopic deroofing. However, cysts located in the posterosuperior segments are considered poor candidates for this procedure. Gastrointestinal endoscopes are more flexible and able to reach less accessible areas than laparoscopes. This study aimed to evaluate the utility of endoscopic transgastric hepatic cyst deroofing (ETGHCD) for treatment of simple hepatic cysts.Patients and methods Seven patients with simple hepatic cysts were evaluated between June 2021 and October 2023. The success rate, procedure time, post-procedure length of hospital stays, complications, pathologic diagnosis, and efficacy were recorded.Results Eleven cysts in seven patients (5 men; mean age 65.5 (standard deviation [SD] 8.5) years) were successfully treated without any complications. The mean procedure time was 65.6 minutes (SD 17.2). Mean post-procedure hospitalization was 4.4 days (SD 1.0). The pathologic diagnosis of 11 cysts showed simple hepatic cysts. The size of the cysts was significantly decreased from 337.0 cm3 (SD 528.8) to 5.2 cm3 (SD 6.3) 1 month after ETGHCD. During the median 12.7-month follow-up in seven patients, the cysts showed a 99.6% reduction with no recurrence.Conclusions ETGHCD provided a feasible, safe, effective, and minimal invasive alternative approach for the treatment of simple hepatic cysts.